2015
DOI: 10.1080/09397140.2015.1020608
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofChrysochus asclepiadeus(Pallas, 1773) (Coleoptera: Chrysomelidae) in Turkey: two distinct subspecies or the same taxon with slightly different populations?

Abstract: According to the literature, Chrysochus asclepiadeus (Pallas, 1773) is represented by two subspecies in the western Palaearctic, including C. asclepiadeus asiaeminoris De Monte, 1948, which was described from south-western Turkey but has not been recorded since 1948. Recently collected specimens from the provinces of İzmir and Isparta (not far from the type locality of C. asclepiadeus asiaeminoris) were compared with specimens of the nominate subspecies from Kiev (Ukraine). It is concluded that C. asclepiadeus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The insect was most probably entered to Iraq from neighboring countries with infected plants. The literature showed that C. herbacea (Duftschmid,1825) is commonly known as The mint leaf Beetle or Green Mint Beetle (2,3,4). It is an aggressive invasive species that is native to the European region and originally described from Austria by Duftschmid in 1825 (5,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The insect was most probably entered to Iraq from neighboring countries with infected plants. The literature showed that C. herbacea (Duftschmid,1825) is commonly known as The mint leaf Beetle or Green Mint Beetle (2,3,4). It is an aggressive invasive species that is native to the European region and originally described from Austria by Duftschmid in 1825 (5,6,7).…”
Section: Introductionmentioning
confidence: 99%